Addiction, Self‐Signalling and the Deep Self. (June 2016) - Holton, Richard
Abstract: Addicts may simply deny that they are addicted; or they may use self‐signalling to try to provide evidence that giving up is not worthwhile. I provide an account that shows how easy it is to provide apparent evidence either that the addiction is so bad that it cannot be escaped; or that there is no real addiction, and hence nothing to escape. I suggest that the most effective way of avoiding this is to avoid self‐signalling altogether.